Monitoring the agri-food system in Myanmar: Agricultural input retailers – September 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of COVID-19 and political instability on Myanmar’s agricultural input sector, a phone survey of 123 input retailers throughout the country was conducted in September 2021. Key findings: Input prices, especially fertilizer, have soared compared to a year ago due to a combination of higher international prices, depreciation of the Myanmar Kyat, and higher freight and domestic transport costs. Faced with price increases of 76 percent on average for compound fertilizer and 132 percent for urea (compared to a year ago), farmers reduced their purchases by 38 percent and 42 percent, respectively. If the decline in fertilizer sales is extended to all of Myanmar, estimated monsoon crop production may fall by 8 percent to 12 percent, equivalent to between $670 million and $1 billion at 2017 prices. Recommendations: The post-monsoon cropping season will be an important opportunity to partially compensate for lower monsoon season production. There is no indication that international fertilizer prices will fall significantly before planting time, however. A combination of temporary fertilizer subsidies and expanded seasonal credit will likely be necessary to encourage farmers to increase crop production.